2007
DOI: 10.1002/stc.168
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic characteristics and response reduction of the metal-touched type of base-isolator

Abstract: In seismic isolation system for lightweight structures, sufficient effect is not acquired when laminated rubber bearings are used. It is because that the pressure on the surface is small. Since sliding base isolators expect the performance even when the pressure on the surface is small, sliding base isolators are used for lightweight structures. Generally, the frictional coefficients of sliding base isolators are assigned in the range 0.01-0.10. However, it is examined by three-dimensional finite element metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In the study of Nishimura et al [17,18], the experimental damping coefficient, static frictional coefficient, dynamic frictional coefficient and frictional coefficients were assigned as c = 0.03 -0.352, =0.17 -0.22, = 0.07 -0.09, = 0.05 -0.1 respectively. It was also shown that even if = 0.1 -0.2, it could be effective in the case of strong earthquakes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Nishimura et al [17,18], the experimental damping coefficient, static frictional coefficient, dynamic frictional coefficient and frictional coefficients were assigned as c = 0.03 -0.352, =0.17 -0.22, = 0.07 -0.09, = 0.05 -0.1 respectively. It was also shown that even if = 0.1 -0.2, it could be effective in the case of strong earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…Shake table tests were conducted on the same materials and the optimum friction coefficient were found to be 0.1 and 0.2, respectively. Furthermore, Nishimura et al [19] conducted another research on the results of two previous studies, where they investigated a metal-touched type base isolator, for which they assigned the experimental damping coefficient, static frictional coefficient and dynamic frictional coefficient as c = 0.096 -0.153, = 0.17 -0.21, and = 0.11 -0.16, respectively, and used a simulation to evaluate the response reduction effect of a multi-degree-freedom system model. The responses were in the range of 50-80% reduction.…”
Section: Introductionmentioning
confidence: 99%